Global, regional, and national burden of hypertension-induced cardiorenal disease, 1990–2021 and projections to 2050: a systematic analysis for the global burden of disease study 2021 - Lei Yang; Yang Li; TingTing Zeng; Yating Li; Lihui Ding; Hongmei Yue; DePeng Jiang (BMC Public Health)
Abstract Objective To explore the impact of hypertension-induced cardiorenal disease on disability rates and mortality, this study reported the burden of cardiorenal disease caused by hypertension (including hypertensive heart disease [HHD] and hypertensive kidney disease) between 1990 and 2021. Methods Utilizing data from the Global Burden of Disease (GBD) database, this study delivered a comprehensive analysis of the burden of hypertension-induced cardiorenal disease. Hypertension was estimated in terms of disability-adjusted life years (DALYs) and mortality, age-standardized death rates (ASDRs), and age-standardized DALY rates (ASRs), considering age, gender, geographical distribution, socio-demographic index (SDI), and cardiorenal disease. Additionally, the estimated annual percentage change (EAPC) was calculated to assess trends in ASDRs and ASRs from 1990 to 2021. Results In comparison with 1990, the mortality and DALYs of hypertension-induced cardiorenal disease rose in 2021, resulting in 1,332,099 deaths and 25,462,184 DALYs of HHD, as well as 454,358 deaths and 10,850,728 DALYs of chronic kidney disease(CKD). Between 1990 and 2021, the ASDRs and ASRs of hypertensive heart disease decreased by 21.99%(95% UI, -31.92-6.74%) and 25.81%(95% U, -34.45- -10.07%), respectively. In contrast, the ASDRs and ASRs of hypertension-attributable CKD decreased by 29.21%(95%UI, 11.55–39.65%) and 19.15%(95% UI, 4.31–27.76%), respectively. In 2021, the highest ASDR and ASR of HHD were recorded in Central Sub-Saharan Africa and Southern Sub-Saharan Africa, while those of hypertension-attributable CKD peaked in Western Sub-Saharan Africa and Southeast Asia. Projections indicate a continued decline in HHD ASDRs through 2050, whereas hypertension-attributable CKD is expected to exhibit an upward trend over the same period. Conclusion Despite the declining mortality rate of HHD, the increasing incidence of hypertension-induced CKD underscores that hypertension-attributable cardiovascular and kidney diseases remain a globally urgent public health concern.